일반 양질 토양 및 캘리포니아 모래 지반에서 현장 투수측정기를 이용한 투수속도와 정수위 포화투수계수 비교 - 김경남(Kyoung Nam Kim) (Weed & turfgrass science, 2022)
본 연구는 일반 토양의 기존토 지반과 캘리포니아 모래 지반에 조성한 잔디밭에서 현장 투수속도기를 이용한 투수속도와 정수위 투수시험기를 이용한 포화투수계수를 비교해서 지반 및 측정방법에 따라 투수성능 차이를 파악해서 잔디식재 및 관리에 활용하고자 시작하였다. 일반 기존토 지반 및 캘리포니아 지반에서 현장 투수속도 및 포화투수계수를 분석결과 지반, 계절 및 측정방법에 따라 유의한 차이가 나타났다. 현장 투수측정기로 조사한 연중 전체 평균 투수속도는캘리포니아 모래 지반이 397.15 mm h-1, 기존토 지반이 1.13 mm h-1로 지반간 차이가 396.02 mm h-1로 나타나서, 캘리포니아 지반의 투수속도가 일반 토양에 비해 350배 더 빠른 것으로 나타났다. 또한 계절별 현장 투수속도도 캘리포니아 모래지반이 195-1398배 더 빠르게 나타났다. 전체 평균 포화투수계수는는 캘리포니아 지반 및 기존토 지반에서 각각 414.77, 122.80 mm h-1로 지반간 차이가 291.97 mm h-1로 캘리포니아 지반이 2.37배 정도 더 빠른 것으로 나타났다. 또한 식재층 지반 유형과 측정방법에 따라 투수성능 차이가 크게 나타났다. 특히, 기존토 지반의 경우 측정 방법에 따라 투수속도 차이가 108배 정도 나타나서 현장 투수속도기를 일반 토양에 사용하는 것은 부적합한 것으로 판단되었다. 잔디밭에서 통기성 및 배수성능을 고려 시 일반 양토의 기존토 지반에 비해 캘리포니아 모래 지반이 더 우수한 것으로 판단되었으며, 기존토 지반은 잔디밭 시공 및 관리 시 모래 혼합을 통해서 식재층의 대공극 비율을 높이는 것이 바람직하다. 본 실험을 통해 밝혀진 지반에 따른 계절별 투수속도와 포화투수계수 데이터는 잔디밭 설계, 시공 및 관리에 실무적으로 유용하게 활용될 수 있을 것이다. This research was initiated to compare water permeability rate measured by both on-site infiltrometer and constant-head permeameter under anysoil (loamy sand soil) and California systems and provide practical information applicable to turfgrass establishment and management. Significant differences were observed in water infiltration rate with soil system, season and method. Overall water permeability rate measured by on-site infiltrometer was 397.15 mm h-1 in California system and 1.13 mm h-1 in anysoil system, being 396.02 mm h-1 in differences. This rate was 350 times higher in California system over anysoil system. Regardless of season, California system showed rapid infiltration rate from 195 to 1,398 times higher than anysoil system. Data from constant-head permeameter indicated that overall average values of saturated infiltration rate were 414.77 and 122.80 mm h-1 for California system and anysoil systems, respectively, which were 291.97 mm h-1 in differences between two soil systems. This data means 2.37 times faster in California system over anysoil system. From this study, water permeability rate greatly varied with soil system and methods. Specially, the rate measured by on-site infiltrometer was 108 times lower under anysoil system of loamy soil when compared with that by constant head method. Use of on-site infiltrometer is not recommended for anysoil system. Considering soil aeration and drainage capacity, a sand-based system was better for turfgrass quality than loamy soil. Accordingly, it should be improved by mixing sand to increase macropore content in rootzone layer under anysoil system of loamy soil. Information on seasonal water permeability rate and saturated infiltration rate under both soil systems practically useful for turfgrass establishment and management. KCI Citation Count: 0